2013
DOI: 10.1088/2040-8978/15/7/075401
|View full text |Cite
|
Sign up to set email alerts
|

Channel-drop filter based on a photonic crystal ring resonator

Abstract: Photonic crystal ring resonators are promising candidates for realizing all optical filters with acceptable transmission efficiency and quality factor values. In this paper, by putting a hexagon-shaped structure at the middle of on 7 × 7 square cavity we created a ring resonator structure and designed a channel drop filter. The drop wavelength of our filter is at 1550.4 nm, with transmission efficiency and quality factor equal to 94% and 707, respectively. Our structure is composed of dielectric rods immersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…So PhCRR structure can perform filtering behavior. It has been shown that the resonant wavelength of PhCRRs depends on the refractive index and structural parameters of the ring core structure [19]. This property has been used for designing optical demultiplexers, by employing multiple resonant rings with different structural parameters in a single structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…So PhCRR structure can perform filtering behavior. It has been shown that the resonant wavelength of PhCRRs depends on the refractive index and structural parameters of the ring core structure [19]. This property has been used for designing optical demultiplexers, by employing multiple resonant rings with different structural parameters in a single structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that by changing the effective length of the resonant cavity, the output wavelength of the filter can be tuned. Another optical filter using resonant cavity based on photonic crystal structures has been proposed using a periodic structure, in which a 2D ThueMorse structure is used [18]. The resonant part of the filter in this work is an L4 cavity, but the transmission efficiency was much higher than the periodic structure [19].…”
Section: Introductionmentioning
confidence: 88%
“…Resonant cavities [17] and ring resonators [18,19] are the most popular structures used for designing all optical photonic crystal based filters. Alipour et al [17] studied the filtering properties of an L4 resonant cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their photonic band gap (PBG) region, photonic crystals (PhCs) have the excellent ability to confine and control the light waves inside compact waveguides [1,2]; therefore, they are very promising structures to design compact optical devices such as optical filters [3][4][5][6], demultiplexers [7][8][9][10], decoders [11,12], gates and switches [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%